Activation of human neutrophils by Esenbeckia leiocarpa: comparison between the crude hydroalcoholic extract (CHE) and an alkaloid (Alk) fraction - de Liz Rafael; Horst Heros; Pizzolatti Moacir; Fröde Tânia; Girard Denis (BMC, 2012)
Abstract Esenbeckia leiocarpa, a wide spread native Brazilian tree, was reported recently to possess anti-inflammatory effects in vivo, but the mechanisms involved are still not fully understood and its role in neutrophils is poorly documented. The aim of this study was to compare the effects of a crude hydroalcoholic extract (CHE) and an alkaloid-enriched (Alk) fraction obtained from Esenbeckia leiocarpa bark on human neutrophils by investigating the effect of each fraction alone or in a mixture with classical neutrophil agonists. CHE inhibited intracellular reactive oxygen species (ROS) production but increased the extracellular superoxide (O2-) production, while Alk increased the former and also slightly increased O2- production. We found that CHE and Alk also induced phagocytosis accompanied by Syk activation, adhesion and degranulation. However, neither CHE nor Alk potentiated the effect of classical neutrophil agonists, namely the cytokines GM-CSF for phagocytosis and TNF-α for adhesion or N-formyl-methionyl-leucyl-phenylalanine (fMLP) for degranulation. In addition, based on catalase treatment, CHE and Alk induced neutrophil apoptosis by a hydrogen peroxide (H2O2)-dependent mechanism. Since the elimination of apoptotic neutrophils by professional phagocytes is important for the resolution of inflammation, the ability of CHE and Alk to induce neutrophil apoptosis has to be considered as one possible mechanism associated with the anti-inflammatory activity of these fractions previously reported in vivo.